Safety and efficacy of 30% hydrogen peroxide in seborrheic keratoses – A prospective and interventional study - Noushin, Shaik; Velusamy, Breethiga; Mohan Krishna Reddy Thotli; Thirupathi Usha Rani; Angidi Sushrutha; Madine Makarand (Asian Journal of Medical Sciences, 2024)
Background: Seborrheic keratosis (SK) is a skin condition affecting the keratinocytes. Although various treatment options are available, the need for a simpler topical treatment approach is unmet. Hydrogen peroxide (HP) acts by forming free radicals and initiates apoptosis in cells. Aims and Objectives: The aim of this study was to evaluate the safety and efficacy of 30% HP in SK. Materials and Methods: This study was conducted on patients attending the Dermatology, Venereology, and Leprology at MGM Hospital attached to Kakatiya Medical College, Warangal and Government Medical College Mahabubabad, Telangana, during the period from December 2019 to May 2021. In total, 80 adult patients with SKs were enrolled. The study was approved by the Research Ethics Committee of the MGM Hospital attached to Kakatiya Medical College. This is a prospective and interventional study. Eighty patients will be treated with 30% of HP topically. A photographic record of the pre- and post-treatment appearance of lesions was maintained. Physician’s lesion assessment (PLA) score was evaluated on day 15th and 106th day after treatment. Local skin reactions (LSRs) were divided into mild, moderate, and severe categories. LSR was observed immediately after 2 weeks and 106 days of treatment. Results: Most of the patients were of middle to elderly age group. SK lesions were most common seen over the head and trunk. The dermatosis papulosa nigra variant was the most common. PLA 0 was observed by day 15 in some patients after application. Of 30% HP, faster healing rates were observed in lesions over the face, and middle aged. Conclusion: About 30% HP is a promising option for the treatment of SK.